Internationalisation strategy for education in the 21st century - Saee, John (Journal of Business Economics and Management, 2004)
There has been a sea change in the world economy with perceived far‐reaching consequences on all aspects of human civilization. This dramatic transformation is largely precipitated by the phenomenon of globalization. Baylis and Smith (1997) put forward the notion that globalization has accelerated the process of increasing interconnectedness between societies so much that events in one part of the world have more and more effect on peoples and societies far away. A globalized world, they argue, is one in which political, economic, cultural, and social events become more and more interconnected, and also one in which they have a wider impact. It is a truism to state that globalization means different things to different people. For some, the term is entirely benign; it portrays a process that accelerates economic prosperity for the nations engaged in globalization. However, for others globalization is a plot by multinational companies, which want to exploit third‐world countries’ resources in terms of cheap labor and raw materials. At the same time, these multinational companies undermine national sovereignty of the third‐world countries due to their enormous economic and political powers (Saee, 2004). In this research paper, an attempt is made to critically explore the drivers and the rationale behind the globalization that has also led educational institutions in most countries around the world to develop internationalization strategies for launching their degree offerings internationally. However, the focus of this research paper is on internationalization strategies by the Australian educational institutions that have important lessons for educational institutions of other countries interested in gaining an insight into internationalization strategies of Australian educational institutions. First Published Online: 14 Oct 2010